Development of a Simple, Sensitive and Rapid Quantitative Analytical Method for Lomefloxacin by High Performance Liquid Chromatography (Stamford Journal of Pharmaceutical Sciences, 2011)
An attempt has been made to develop a simple, sensitive and rapid high performance liquid chromatographic (HPLC) method of analysis for lomefloxacin as in pharmaceutical dosage form using 0.025 M phosphoric acid and acetonitrile (80:20) as mobile phases. The mobile phase was used as solvents to dissolve lomefloxacin and 0.0122 mg/mL stock solution was prepared. Lomefloxacin solution was scanned with UV-spectrophotometer and the absorption maximum (λmax) was found to be 287 nm. This method was successfully applied to five eye drop dosage forms of lomefloxacin encoded as pp1, pp2, pp3, pp4 and pp5 marketed by five different pharmaceutical companies and the result was found to be satisfactory and reproducible. The method was validated by spiked recovery experiments and shown to be linear for lomefloxacin. The method can be used for routine analysis in both research laboratories, and pharmaceutical and chemical industries to analyze the drugs and chemicals without any interference by the excipients.   Key words: Lomefloxacin; HPLC; Analysis; Reproducible. DOI: http://dx.doi.org/10.3329/sjps.v4i1.8871 SJPS 2011; 4(1): 69-73